Strategi Taboo for Taboo pada Penerjemahan Kata-Kata Tabu dalam Novel Where There’s Smoke - Ngaliyah, Himmatul; Cholsy, Hayatul (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2024)
The purpose of this research is to analyze taboo for taboo strategy and factors that influence in translating taboo words in the novel Where There's Smoke into Indonesian. The data for this research are taboo words in the novel Where There's Smoke and its translation in Indonesian entitled Pencarian which uses the taboo for taboo strategy in its translation. The taboo for taboo strategy maintains taboo from the source language (SL) into the target language (TL). Data collection techniques are carried out by reading and taking notes. The data analysis in this research is based on Davoodi’s theory (2009). From the research results, it was found that the taboo for taboo strategy can translate taboo words at the same taboo level as SL and taboo for taboo strategy with a lower taboo level than SL. Factors that influence the taboo for taboo strategy are the use of the same function of taboo words between SL and TL, the message and meaning conveyed are the same, the difference language systems of SL and TL, the translator's understanding of the culture of SL, the readers of the target text, translator's sociolinguistic abilities, and editor’s role.